Anti-PD-1 elicits regression of undifferentiated pleomorphic sarcomas with UV-mutation signatures. Issue 6 (8th June 2021) - Cheung, Laurene S; Chen, Lingling; Oke, Teniola F; Schaffer, Thomas B; Boudadi, Karim; Ngo, Jillian T; Gross, John McMahon; Kemberling, Holly; Diaz, Luis A; Lipson, Evan; Sidhom, John-WIlliam; Taube, Janis; et al.
Abstract : Undifferentiated pleomorphic sarcoma (UPS), an aggressive soft-tissue sarcoma of adults, has been characterized by low tumor mutational burden (TMB) and high copy number alterations. Clinical trials of programmed death-1 (PD-1) blockade in UPS have reported widely varying efficacy. We describe two patients with recurrent scalp UPS that experienced clinical benefit from PD-1 blockade. These tumors had high TMB with a UV-induced mutational pattern. Analysis of additional head and neck UPS cases identified five out of seven tumors with high TMB and an ultraviolet (UV) mutational signature. Head and neck UPS tumors also had increased programmed death-ligand 1 (PD-L1) expression and CD8+ T cell infiltration as compared with UPS tumors arising from other sites. In summary, we found that UPS tumors of the head and neck, but not elsewhere, have a PD-L1+, T-cell-inflamed tumor microenvironment and high TMB, suggesting that these tumors represent a distinct genetic subgroup of UPS for which immune checkpoint inhibitor therapy might be effective.